Bridging the Gap Between Second Language Acquisition Research and Memory Science: The Case of Foreign Language Attrition - Mickan, Anne; McQueen, James M.; Lemhöfer, Kristin (Frontiers in Human Neuroscience, 2019)
The field of second language acquisition (SLA) is by nature of its subject a highly interdisciplinary area of research. Learning a (foreign) language, for example, involves encoding new words, consolidating and committing them to long-term memory, and later retrieving them. All of these processes have direct parallels in the domain of human memory and have been thoroughly studied by researchers in that field. Yet, despite these clear links, the two fields have largely developed in parallel and in isolation from one another. The present paper aims to promote more cross-talk between SLA and memory science. We focus on foreign language (FL) attrition as an example of a research topic in SLA where the parallels with memory science are especially apparent. We discuss evidence that suggests that competition between languages is one of the mechanisms of FL attrition, paralleling the interference process thought to underlie forgetting in other domains of human memory. Backed up by concrete suggestions, we advocate the use of paradigms from the memory literature to study these interference effects in the language domain. In doing so, we hope to facilitate future cross-talk between the two fields, and to further our understanding of FL attrition as a memory phenomenon.